Implementation of Qur’anic Reading and Writing Learning Strategies at MDTA Al-Hasanah Aek Tampang Padangsidimpuan - Nurul Fadilah Siagian (Yayasan Tahfidzul Qur'an Al-Fawwaz, 2026)
This study analyzes the implementation of Qur’anic Reading and Writing learning strategies, referred to as BTQ, at MDTA Al-Hasanah Aek Tampang Padangsidimpuan, including its supporting factors, inhibiting factors, and teacher responses to learning obstacles. The study employed a descriptive qualitative approach. Data were collected through classroom observation, semi-structured interviews with the madrasah head, BTQ teachers, and selected students, as well as documentation of learning activities and institutional records. Data were analyzed through data condensation, data display, and conclusion drawing, supported by triangulation and member checking. The findings show that BTQ learning is implemented through religious habituation, classical instruction, the Iqra’ method, talaqqi-based guidance, drill and practice, demonstration, individualized assistance, writing exercises, and periodic evaluation. Drill and demonstration are the dominant strategies because they enable students to listen, imitate, repeat, and correct Qur’anic pronunciation under teacher supervision. Supporting factors include leadership support, student enthusiasm, a religious environment, learning media, and parental involvement. Obstacles include varied reading ability, limited time, insufficient home practice, and student concentration. The study concludes that BTQ learning requires adaptive, repetitive, and teacher-guided strategies supported by institutional commitment and family collaboration.